Performance and Emission Characteristics of Jatropha Biodiesel Blends in a Direct Injection CI Engine - Bhatta, Khem Raj; Karna, Rupesh Lal; Jha, Ajay Kumar; Adhikari, Surya Prasad (Himalayan Journal of Applied Science and Engineering, 2021)
The Jatropha seed oil is non edible, contains high amount of oil and less expensive feedstock. So, in this study a methyl ester biodiesel was produced from Jatropha seed oil following two step transesterification process using methanol, sulphuric acid and sodium hydroxide. The effect of Jatropha biodiesel blends and petroleum-based diesel on the performance and emission of four strokes, naturally aspired, water cooled and a direct injection diesel engine at five engine loads with a constant engine speed of 1500 rpm were examined. The physical and thermal properties of 20 % Jatropha-biodiesel and 80 % diesel (JB20) were tested on American Society for Testing and Materials (ASTM) standards and found to be within the standard. The engine performance parameters for biodiesel blends such as Indicated Power (IP), Brake Thermal Efficiency (BTE), Brake Specific Fuel Consumption (BSFC), Torque, Mechanical Efficiency (ME) and Exhaust Gas Temperature (EGR) were obtained and compared   with diesel fuel. At higher load, the IP of 15 % Jatropha-biodiesel and 85 % diesel (JB15) is lower than diesel and other blends. BTE of 10 % Jatropha-biodiesel and 90% diesel (JB10) increases to 5 % mainly on 50 % loading condition and at higher loading BTE of diesel is higher than jatropha biodiesel blends. For Jatropha biodiesel blends SFC was 19 % higher than diesel but at high load, SFC was nearly same for all test fuels. Mechanical efficiency of JB15 was found to be 18 % higher than diesel at higher loading. The highest exhaust gas temperature was 352.46 0C, 358.61 0C, 353.51 0C and 343.79 0C for diesel, JB10, JB15 and JB20, respectively at 3kW loading. Also, experimental results show that the smoke opacity reduced by 31.6 % with JB20 compared to diesel. From the fuel property, engine performance and emission characteristics, it is concluded that the Jatropha biodiesel up to 20 % can be blended with diesel and can be used as an alternative fuel in existing diesel engine without any modification.